Metagenome-assembled genome of a Chitinophaga sp. and its potential in plant biomass degradation, as well of affiliated Pandoraea and Labrys species - Funnicelli, Michelli Inácio Gonçalves [UNESP]; Pinheiro, Daniel Guariz [UNESP]; Gomes-Pepe, Elisângela Soares [UNESP]; de Carvalho, Lucas Amoroso Lopes [UNESP]; Campanharo, João Carlos [UNESP]; Fernandes, Camila Cesário [UNESP]; Kishi, Luciano Takeshi [UNESP]; Carareto Alves, Lúcia Maria [UNESP]; de Macedo Lemos, Eliana Gertrudes [UNESP] (Springer Nature, 2021)
The prospection of new degrading enzymes of the plant cell wall has been the subject of many studies and is fundamental for industries, due to the great biotechnological importance of achieving a more efficient depolymerization conversion from plant polysaccharides to fermentable sugars, which are useful not only for biofuel production but also for various bioproducts. Thus, we explored the shotgun metagenome data of a bacterial community (CB10) isolated from sugarcane bagasse and recovered three metagenome-assembled genomes (MAGs). The genomic distance analyses, along with phylogenetic analysis, revealed the presence of a putative novel Chitinophaga species, a Pandoraea nosoerga, and Labrys sp. isolate. The isolation process for each one of these bacterial lineages from the community was carried out in order to relate them with the MAGs. The recovered draft genomes have reasonable completeness (72.67–100%) and contamination (0.26–2.66%) considering the respective marker lineage for Chitinophaga (Bacteroidetes), Pandoraea (Burkholderiales), and Labrys (Rhizobiales). The in-vitro assay detected cellulolytic activity (endoglucanases) only for the isolate Chitinophaga, and its genome analysis revealed 319 CAZymes, of which 115 are classified as plant cell wall degrading enzymes, which can act in fractions of hemicellulose and pectin. Our study highlights the potential of this Chitinophaga isolate provides several plant-polysaccharide-degrading enzymes.
Keywords: Genome assembly; Glycosil hidrolases; Hemicellulose; Microorganism; Sugarcane